Factors Influencing The Course Preference of Senior High School STEM Strand Graduates Enrolled in Non-STEM Degrees - Serad, A’ishah G. Hadji; Basher, Salamah M. (Education, Science, and Technology International Conference, 2025)
This study aimed to determine the factors that influence the course preferences of Senior High School (SHS) graduates from the Science, Technology, Engineering, and Mathematics (STEM) strand who chose to enroll in non-STEM degrees. The study used mixed-method research design. The respondents were the SHS STEM strand graduates of Marawi City National High School enrolled in non-STEM degrees in different higher education institutions in Marawi City. Findings revealed that most of these students had a very satisfactory academic performance in SHS, with general averages ranging from 85–89. Majority of the respondents were enrolled in private colleges. Most of their parents were college graduates, and many fathers worked as vendors or farmers, while most mothers were housewives. The typical family income ranged from ₱5,001 to ₱10,000 monthly. The most chosen non-STEM degrees were Social Work, Education, and Criminology. The study identified two major categories of influencing factors: social and individual. Social factors included university considerations, perceived usefulness of the course, and social considerations. Individual factors encompassed personal interest, the influence of surrounding and geographic location. The study found that personal and social factors were more influential than academic or economic backgrounds. Students were strongly influenced by their own interests, peer advice, perceived job opportunities, and the convenience of the school location. However, Academic performance and parents’ socio-economic status did not significantly influence their course choices. The study concludes that the course decisions of the STEM graduates who pursued non-STEM degrees is largely influenced by personal interest, peer advice, perceived job opportunities, and convenience rather than academic performance and parental socio-economic status.